2019
DOI: 10.3390/fluids4010013
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Natural Hydraulic Lime Grouts for Conservation of Stone Masonry—Influence of Compositional and Processing Parameters

Abstract: This review provides an overview of the recent progress in the field of the rheology of grouts for historic masonry consolidation. During the last two decades, significant research has been devoted on the grouting technique for stone masonry consolidation but most results are scattered by scientific papers, congress communications, and thesis. This paper compiles and briefly demonstrates the effect of several intrinsic and extrinsic parameters, such as admixtures, additions, pressure, temperature, and measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Over the years, useful progress has been made in applied rheology and different rheological models have been suggested [32][33][34][35][36][37][38]. The most popular rheological models that have been proposed to describe suspensions with yield stress are the Bingham, Casson and Herschel-Bulkley [3,[35][36][37]. However, there is no single model that can adequately describe the behavior of all complex suspensions, in addition to the fact that none of these models have a limit on the maximum shear stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, useful progress has been made in applied rheology and different rheological models have been suggested [32][33][34][35][36][37][38]. The most popular rheological models that have been proposed to describe suspensions with yield stress are the Bingham, Casson and Herschel-Bulkley [3,[35][36][37]. However, there is no single model that can adequately describe the behavior of all complex suspensions, in addition to the fact that none of these models have a limit on the maximum shear stress.…”
Section: Methodsmentioning
confidence: 99%
“…The grout's injectability appears to be one of the most crucial characteristics in the grouting's performance. In this context, rheology is used as a tool in the design and quality control of the injection grout [2,3]. Cementitious-based grouts are known for having a complex rheology [4,5], because interaction between the binder particles and grout hydration generates a microstructure that leads to a yield stress that is not constant over time.…”
Section: Introductionmentioning
confidence: 99%
“…It is a demonstration that the collapsed system takes a while to rebuild in the absence of stress. 43 The maximum shear stress from the lowest to the highest investigated temperatures are 43.39, 39.58, 37.69, 35.19, and 34.33 lb/100 ft 2 . It is observed that the shear stress decreased with the increasing temperature.…”
Section: Thixotropic Behavior Of the Lightweight Slurry Atmentioning
confidence: 86%
“…An appropriate way to characterise a thixotropic system is to use the hysteresis loop of the flow curve, representing an applied shear stress (upward) followed by a relaxing of the stress (downward) [58]. Figure 7 represents a 1D single hysteresis loop analogous to fig.…”
Section: Constitutive Modelmentioning
confidence: 99%